Very low levels of high density lipoprotein cholesterol in four sibs of a family with non-neuropathic Niemann-Pick disease and sea-blue histiocytosis. Issue 8 (August 1990) - Viana, M B; Giugliani, R; Leite, V H; Barth, M L; Lekhwani, C; Slade, C M; Fensom, A
Abstract : Very low serum levels of high density lipoprotein cholesterol ranging from 8.6 to 13.9 mg/dl were detected in four out of 12 sibs of a Brazilian kindred with the non-neuropathic form of Niemann-Pick disease. Hepatosplenomegaly, interstitial infiltration of the lungs, absence of neurological signs, sea-blue histiocytes in the bone marrow and liver, and high values for serum acid phosphatase (18 to 32 U/l) were common to all affected children. Leucocyte acid sphingomyelinase activity ranged from 3.6 to 6.5% of mean control values, and fibroblast activity from 9 to 13% of mean controls. The parents had low-normal levels. The relationship between these findings is unclear and deserves further investigation.